دور الإعلام الریاضي المكتوب في تنمیة القیم لدى الشباب - دراسة میدانیة - بالهادي, هاجرة (University of eloued جامعة الوادي, 2015)
تناولت ھذه الدراسة موضوعا ھاما وھو دور الإعلام الریاضي المكتوب في تنمیة القیم لدى الشباب - دراسة میدانیة – على عینة من شباب ولایة الوادي، بھدف الإجابة عن التساؤلات المطروحة للوصول إلى أھداف ونتائج المحققة في دور الإعلام الریاضي في تنمیة القیم لدى الشباب، وقد اشتملت الخطة على أربع فصول. المقدمة والفصل التمھیدي الذي یشمل على الإشكالیة وأسباب اختیار الموضوع وفرضیات الدراسة والأھمیة والأھداف والمصطلحات الدراسة والدراسات السابقة وإجراءات الدراسات ومنھجھا، ولقد كان اختیاري للعینة العشوائیة من 200 عینة، أما المنھج فقد اخترت المنھج الاستقرائي الوصفي المقارن. الفصل الأول: الذي كان بعنوان الإعلام الریاضي المكتوب، حیث اشتمل على مبحثین فالأول تحدثت فیھ عن ما ھیة الإعلام، أما الثاني فصلت فیھ ما ھیة الصحافة الریاضیة. أما الفصل الثاني فكان من نصب الجزء الثاني من عنوان بحثي ألا وھو علاقة الإعلام الریاضي بالقیم لدى الشباب، فقسمتھ كذلك إلى مبحثین أول عن ما ھیة القیم والثاني فخصصتھ عن ما ھیة الشباب. الفصل الثالث: خصصت ھذا الفصل لدراسة المیدانیة، والتي باعتبارھا الجزء الأھم من الموضوع البحث، حیث تم تحلیل النتائج ومناقشتھا. This study deals with an important subject which is the role of sports media written in values development among young people - Study field - a sample of the youth of the mandate of the valley, in order to answer the questions posed to reach the goals and the results achieved in the role of sports media in values development among young people, included plan four .seasons Provided preliminary separation which includes the problem and the reasons for choosing the topic and hypotheses of the study and the importance, objectives and terminology study and previous studies and procedures Studies and approach, and it was optional random from 200 samples of the sample, the .method I chose inductive descriptive comparative Chapter One: which was written titled sports media, where the former included two sections talked about 'What is the media, .and the second separated the' What sports journalism The second chapter of the monument was the second part of the title of research, namely the sports media relationship values among young people, Vksmth well as to the first two sections of what deity values and the second Fajssth about .'What is the youth Chapter III: This chapter devoted to the study of the field, which as the most important part of the subject search, where the .results were analyzed and discussed
ماستر دعوة
Keywords: الشباب/تنمیة القیم/الإعلام الریاضي; Youth/Value Development/Sports Media